Home Fitness Mobile Application - Koh, Qing Zhe (2022)
As the pandemic COVID-19 spread wildly all over the world. Due to this situation, the Malaysian government, led by Prime Minister Muhyiddin Yassin, enacted a statewide lockdown known as the Movement Control Order (MCO) on March 18, 2020, in reaction to the increase in instances. All outdoor activities and exercise are prohibited during the MCO period. So, there will be an issue for those who want to exercise and go to the gym workout but don’t have any knowledge and equipment to workout. This project aims to provide the home workout exercise video as a guide for them to workout at home. Hence, they could have at home during this period. After researching some existing applications, the limitations of these applications are discovered as their application’s workout videos are required equipment such as dumbbells, barbells or leg press machines. Besides, these applications are either specific for men or specific for women. Therefore, this proposed application will provide fitness exercise videos without any equipment to men and women. There is a platform for users to share their feelings about their workout on it. Users can communicate with each other posts during this period. Agile methodology consisting of Plan phase, Design phase, Development phase, Test phase, Deployment phase and Review phase will be implemented in the development of the application. After the development phase, User Acceptance Test (UAT) is conducted to detect defects and errors in the application. The application will then be released and collect feedback from users.